The Effect of Different Root Canal Irrigants When Activated With Endoactivator and Manual Dynamic Agitation on Enterococcus Faecalis- A Comparative in Vitro Evaluation (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: Efaecalis; endo activator; manual dynamic agitation; aloe vera; Q Mix